2020
DOI: 10.3727/152599519x15506259856101
|View full text |Cite
|
Sign up to set email alerts
|

Motivating and Retaining Festival Patronage

Abstract: Globally, festivals and host communities face increased competition each year from one another and from the myriad of alternate entertainment options. To remain competitive, festival organizers must fully understand what keeps festival attendees coming back year after year. Festivalscape has been an emerging concept of value in this arena, and previous studies have found that festivalscape has an effect on the attendees' emotion and behavior that influences their overall perceived value of the festival. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Other important results from the model included three of four festivalscape factors (food/ beverage quality, festival staff, facility) influencing satisfaction. This confirms prior research that indicate a significant relationship between festivalscape and satisfaction (Bruwer and Kelley, 2015;Chou et al, 2018;Yoo et al, 2020). The festivalscape factor convenience did not influence satisfaction.…”
Section: Ei Theory and Craft Beer And Food Festivalsupporting
confidence: 89%
See 1 more Smart Citation
“…Other important results from the model included three of four festivalscape factors (food/ beverage quality, festival staff, facility) influencing satisfaction. This confirms prior research that indicate a significant relationship between festivalscape and satisfaction (Bruwer and Kelley, 2015;Chou et al, 2018;Yoo et al, 2020). The festivalscape factor convenience did not influence satisfaction.…”
Section: Ei Theory and Craft Beer And Food Festivalsupporting
confidence: 89%
“…Festivalscape → satisfaction Previous literature has demonstrated that festivalscape factors influence festival attendees' satisfaction. For example, Yoo et al (2020) found that the festivalscape factors were important to attendees' satisfaction with a festival. Bruwer and Kelley (2015) explored four key domains of the festivalscape that were positively correlated with satisfaction: (1) generic festival features and festival staff, (2) entertainment and catering, (3) comfort amenities and (4) festival venue and information.…”
Section: Enduring Involvement → Satisfactionmentioning
confidence: 99%
“…Due to the highly profitable and benevolent nature of food festivals, achieving a competitive edge and ensuring the viability of festivals is a major challenge for festival organizers (Kruger et al. , 2010; Yoo et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Holding food festivals promotes a destination's food culture, boosts the local economy and stimulates domestic/local agriculture (Organ et al, 2015). Due to the highly profitable and benevolent nature of food festivals, achieving a competitive edge and ensuring the viability of festivals is a major challenge for festival organizers (Kruger et al, 2010;Yoo et al, 2020). Nevertheless, food festivals often fail because of poor design such as lack of food innovation and variety, long lines and waiting time, an overcrowded, rowdy environment and an insufficient or unappealing food supply (Culha, 2020;Mykletun, 2011).…”
Section: Introductionmentioning
confidence: 99%